Chromatogram Profiles and Cytotoxic Activity of Irradiated Mahkota Dewa (Phaleria Macrocarpa (Scheff.) Boerl) Leaves - E. Katrin; Selvie Selvie; H. Winarno (PPIKSN-BATAN, 2011)
Gamma irradiation has been used by the industries for preservation of herbal medicine, but it has not been studied the effect of gamma irradiation on their efficacy, especially their bioactivity as anticancer substances. The purpose of this research was to study the effect of gamma irradiation on the mahkota dewa leaves which has been claimed to contain potent anticancer substances. Maceration of dried mahkota dewa leaves successively with n-hexane, ethyl acetate, and ethanol gave crude extracts which the ethyl acetate was the most cytotoxic extract against leukemia L1210 cells with an inhibition concentration fifty (IC50) value of 10.3 µg/ml. Further separation of ethyl acetate extract by column chromatograph gave 7 fractions, and fraction 2 showed the most cytotoxic fraction exhibited the most cytotoxic extract against leukemia L1210 cells with an IC50 value of 1.9 µg/ml. Since, the fraction 2 of ethyl acetate extract was the most potent fraction, the irradiated samples were treated with the same procedure as treatment of fraction 2 from control sample. Cytotoxic activity test of fractions 2 from irradiated samples showed that the cytotoxic activity decreased depending on increasing of irradiation dose. Gamma irradiation dose up to 7.5 kGy on mahkota dewa leaves could decreased the cytotoxic activity of fraction 2 as the most cytotoxic-potential fraction against leukemia L1210 cells, but decreasing the cytotoxic activity has not exceeded the limit of the fraction declared inactive. So that the irradiation dose up to 7.5 kGy can be used for decontamination of bacteria and fungus/yeast without eliminating the cytotoxic activity. Gamma irradiation also caused changes in the thin layer chromatograph (TLC) spots and HPLC chromatograms profiles of fraction 2 which was the most cytotoxic fraction in ethyl acetate extract of mahkota dewa leaves against leukemia L1210 cells. One of the main peaks (peak 1) on HPLC chromatograms decreased with increasing the irradiation dose. In agree with the decreasing peak 1 in chromatogram of fraction 2 due to irradiation, cytotoxic activity of fraction 2 also decreased along with increasing doses of irradiation. It suggested that peak 1 is the component that contributes to the cytotoxic activity of fraction 2 in ethyl acetate extract of mahkota dewa leaves.Received: 20 November 2010; Revised: 06 April 2011; Accepted: 14 April 2011